The Textile Building, New York World's Fair 1939 (Curt Teich & Co.)
Covering an acre and a half of ground adjacent to the Long Island Railroad and two Fair entrances, this modern structure will contain displays of fabrics, patterns and textile machinery. The end wall of the ""fin"" will be used as a screen on which five-minute movies will be flashed.